The role of clothing in participation of persons with a physical disability: a scoping review protocol. Issue 3 (8th March 2018) - Esmail, Alida; Poncet, Frédérique; Rochette, Annie; Auger, Claudine; Billebaud, Christophe; de Guise, Élaine; Ducharme, Isabelle; Kehayia, Eva; Labbé, Delphine; Dahan-Oliel, Noémi; Lessard, Isabelle; Vermeersch, Olivier; et al.
Abstract : Introduction: Clothing is an important aspect of nearly all human societies from performing social and cultural functions to indicating social status, a form of protection and a way for self-expression. It can help or hinder the ability to fulfil everyday activities and social roles and with the rising industry of wearable technologies, smart textiles are adding health-monitoring functions to clothing. The influence that clothing can have on the life of someone with a physical disability is significant, and further research is needed to understand it better. To achieve this, a scoping review will be performed with the aim of understanding the role of clothing in participation (ie, at home, in the community, etc) of individuals with a physical disability. This article presents the protocol and procedure to be adopted. Methods and analysis: An in-depth iterative analysis of the scientific literature from six databases (MEDLINE, Embase, CINAHL, Scopus, PsycINFO and ERIC) as well as a hand search of grey literature and reference lists will be performed. After an abstract and full-text review of references by three reviewers independently, data from the selected articles will be tabulated and synthesised with a qualitative and quantitative approach using the International Classification of Functioning, Disability and Health as a unifying conceptual framework. A multidisciplinary consultation group of experts from various stakeholder groups will be involved in multiple steps to ensure validation and relevance of the data. Ethics and dissemination: As this is a review involving analysis of data available in the public domain and does not involve human participants, ethical approval was not required. Results will be presented in a co-constructed format with the expert consultation group to ensure validity and maximise its practicality moving forward. Our dissemination plan includes peer-reviewed publications, presentations and stakeholder meetings.